English Students’ Learning Motivation in Rural Senior High School - Septiana, Safira; Surayya, Siti Ayu; Husnu, Muhammad; Agustina, Yulia (IKIP Siliwangi, 2026)
This research investigates the underlying reasons why grade XI students at MA NWDI Lepak, a senior high school in rural East Lombok Regency, are motivated to learn English. Data were collected through semi-structured interviews and document analysis using a qualitative approach with case studies. The theme analysis method developed by Braun and Clarke (2006) was used to analyze this study. The results show that students' learning motivation is influenced by two main factors: (1) students' sociocultural and identity factors, such as support from teachers, peers, and perceptions of English in the community; and (2) strong future goals, such as career aspirations and educational expectations, which are the main drivers of their motivation. These results support socio-cultural identity theory and potential-based achievement goal theory, which emphasize that students' motivation is influenced by their thoughts about their future potential in their social and cultural contexts. It is hoped that this research will help teachers, schools and policy makers create effective and contextualized English learning strategies for students in rural areas.